Analysis Of The Level Of Effectiveness Of Land And Building Tax Collection Towards Optimizing The Achievement Of The Original Income Target Of The Simalungun District - Ginting, Mitha Christina; Simanjuntak, Arthur; Sagala, Farida; Sagala, Lamria; Butarbutar, Riska Septiani AMT (Jurnal Ilmiah Accusi, 2025)
Effectiveness of Land and Building Tax Collection to Increase Regional Original Income with land and building tax revenue, there are still many shortcomings in it, usually in PBB collections, empty houses are still found, there are double SPPT (Tax Payable Notices), and there are also taxpayers who disobedient. The level of effectiveness of land and building tax revenue from 2019 to 2023 is said to be quite effective with an average percentage of 87.71%. Where the highest effectiveness will occur in 2022 with a percentage of 102.07%. According to the level of effectiveness of land and building tax collection, it can be concluded that the Simalungun Regency Regional Revenue Service has not been completely successful in realizing land and building tax or has not exceeded or achieved the target that has been determined for the last 5 years, which means it has carried out its duties quite effectively